Evaluating Didactic Methods for Training Medical Students in the Use of Bedside Ultrasound for Clinical Practice at a Faculty of Medicine in Romania. (11th September 2015) - Florescu, Cosmin C.; Mullen, Jeffrey A.; Nguyen, Vivian My; Sanders, Brooke E.; Vu, Priscilla Quynh-Phuon
Abstract : Objectives: Medical students' time is limited, so efficiency in medical education is valued. This research project aimed to determine the most effective means to teach bedside ultrasound to medical students in a 1‐week training course. We hypothesized that the best method would include a combination of podcasts and hands‐on teaching; therefore, there would be a statistically significant difference among the various methods of teaching. Methods: Medical students were randomly assigned to 3 groups. All groups attended a 50‐minute hands‐on bedside ultrasound training session. Students in the first group attended a 50‐minute live lecture before the hands‐on session, whereas students in the second group watched a podcast that covered the same material as the live lecture. Students in the third group served as the control and only attended the hands‐on sessions. Five topics were covered during the course: (1) introduction to ultrasound, (2) pulmonary ultrasound, (3) cardiac ultrasound, (4) hepatobiliary ultrasound, and (5) focused assessment with sonography for trauma. Students completed a 20‐question pre‐ and post‐training quiz that covered basic ultrasound principles. Students also conducted a focused assessment with sonography for trauma examination for the practical portion of their evaluation. Results: Students' pre‐ to post‐training quiz scores increased from 33.6% to 72.6% correct in the lecture group (n = 21; P < .0001), from 40.7% to 75.5% correct in the podcast group (n = 20; P < .0001), and from 37.8% to 70.0% correct in the control group (n = 23; P < .0001). Data analysis of written and practical examination scores showed no significant differences among the groups [F(2, 61) = 0.885; P = .418; F(2, 60) = 1.739; P = .184, respectively]. Conclusions: These results suggest that all 3 methods are equally effective in teaching novice medical students basic ultrasound knowledge and skills.